Два новых вида жуков-щелкунов (Coleoptera, Elateridae) из Бадхыза (Южная Туркмения) - Долин, В.Г.; Атамурадов, X.И. (Вестник зоологии, 1980)
Two species of click beteles are described as new: Cardiophorus hiemalis sp. nov. distinct by long thin antennae, absence of a longitudinal process on the pronotum and a short first tarsal segment. Melanotus badchysicus sp. now. differs from group M. humi-lis Schw. by a thin punctuation pronotum, antennal structure and male genitalia.